2021
DOI: 10.1021/acsomega.1c00243
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design of a Reversible Hydrogen Storage Device Composed of the Graphene Nanoflake–Magnesium–H2 System

Abstract: Carbon materials such as graphene nanoflakes (GRs), carbon nanotubes, and fullerene can be widely used for hydrogen storage. In general, metal doping of these materials leads to an increase in their H2 storage density. In the present study, the binding energies of H2 to Mg species on GRs, GR–Mg m+ (m = 0–2), were calculated using density functional theory calculations. Mg has a wide range of atomic charges. In the case of GR–Mg (m = 0, Mg atom), the binding energy of one H2 molecule is close to 0, whereas thos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Magnesium has three valence states as neutral, mono, and divalent states expressed as Mg, Mg + , and Mg 2+ . Here, the molecular devices composed of GNF-Mg were examined as the reversible hydrogen storage device [45].…”
Section: Molecular Design Of Reversible Hydrogen Storage Devicementioning
confidence: 99%
See 2 more Smart Citations
“…Magnesium has three valence states as neutral, mono, and divalent states expressed as Mg, Mg + , and Mg 2+ . Here, the molecular devices composed of GNF-Mg were examined as the reversible hydrogen storage device [45].…”
Section: Molecular Design Of Reversible Hydrogen Storage Devicementioning
confidence: 99%
“…This specific property makes the GNF-Mg-H2 system suitable for use as a H2 storage device with adsorption-desorption reversible properties. In the following sections, the direct AIMD calculations [46][47][48] for the electron and hole capture processes of the GNF-Mg-H2 system are described [45].…”
Section: Electron Capture Dynamics Of Gnf-mg-h2mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we demonstrated that the graphenelithium system can effectively store molecular H 2 . Analogously, the magnesium-based GR-Mg-H 2 system has reportedly been used in a reversible hydrogen-storage device [24].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the S N 2 reaction mechanism in the NF 3 –CH 3 Cl cluster induced by electron capture was investigated using a direct ab initio molecular dynamics (AIMD) method. 37–39 The reaction is expressed asNF 3 –CH 3 Cl + e − → [(NF 3 –CH 3 Cl) − ] ver → NF 2 + CH 3 F + Cl − where [(NF 3 –CH 3 Cl) − ] ver is the structure of (NF 3 –CH 3 Cl) − at the vertical electron capture point of the neutral parent cluster. Fig.…”
Section: Introductionmentioning
confidence: 99%